SCATS (Sydney Coordinated Adaptive Traffic System) As A Solution To Overcome Traffic Congestion in Big Cities - Jaja Kustija; Andharesta Nur Giovannie S (Universitas Komputer Indonesia, 2023)
The development of an urban area should be followed by the arrangement of adequate infrastructure. One of the important needs in an urban area is transportation. An increase in the number of means of transport often creates congestion, especially at intersections. The timing of cycles that do not lead tothe number of vehicles lining up but only based on a balanced division of time is one of the causes of congestion. Based on this background, a system of setting the flame cycle of the lamp u basedon the length of the queue is needed. This study aims to implement the Sydney Coordinat Adaptive Traffic System (SCATS) application as a solution to overcome traffic congestion in DKI Jakarta. The method used is to use quantitative methods with the 1997 Indonesian Road Capacity Manual (MKJI) approach. The results obtained include, the SCATS application can adaptively adjust the cycle time of sensor-based traffic lights. Traffictraffic settings can be manually controlled by the operator remotely using an internet communication network and can be conditioned with special cases or emergencies. Based on the results of the study, the SCATS application is expected to be implemented in all major cities in Indonesia.